2012
DOI: 10.1371/journal.pone.0031937
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Low Levels of Dystrophin on Mouse Muscle Function and Pathology

Abstract: Duchenne muscular dystrophy (DMD) is a severe progressive muscular disorder caused by reading frame disrupting mutations in the DMD gene, preventing the synthesis of functional dystrophin. As dystrophin provides muscle fiber stability during contractions, dystrophin negative fibers are prone to exercise-induced damage. Upon exhaustion of the regenerative capacity, fibers will be replaced by fibrotic and fat tissue resulting in a progressive loss of function eventually leading to death in the early thirties. Wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
96
2
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 101 publications
(111 citation statements)
references
References 42 publications
11
96
2
2
Order By: Relevance
“…1,2 The symptoms of this disease occur in infancy, with the necrosis of skeletal muscle fibers, muscle fibrosis, and the infiltration of adipose tissue. 3,4 In dystrophic muscle, the degenerative process occurs by oxidative stress and the loss of homeostasis combined with the synthesis of free radicals that contribute to skeletal muscle necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The symptoms of this disease occur in infancy, with the necrosis of skeletal muscle fibers, muscle fibrosis, and the infiltration of adipose tissue. 3,4 In dystrophic muscle, the degenerative process occurs by oxidative stress and the loss of homeostasis combined with the synthesis of free radicals that contribute to skeletal muscle necrosis.…”
Section: Discussionmentioning
confidence: 99%
“…[21][22][23][24][25] Moreover, low dystrophin levels in transgenic mice models and patient cohorts have been demonstrated to bring pathological and functional benefits, at least slowing down or preventing disease development. 25,26 In addition, the contribution from soluble paracrine molecules secreted from the injected cells rather than from the presence on dystrophin has to be mentioned. It is likely that in the first year of treatment the amelioration seen in the GRMD dogs injected with autologous LV ex6-8 133+musSCs was due to two uneven components: (i) a burst release of stimulating and restoring muscle factors from injected cells and the recipient tissue, and (ii) an initial low dystrophin expression.…”
Section: Discussionmentioning
confidence: 99%
“…All these approaches have many hurdles to overcome if a comprehensive and effective treatment for DMD is to be found. All muscles including cardiac, skeletal, and smooth muscle need to be targeted; reports have suggested that dystrophin levels of more than 20% in mice are needed to protect muscles from exercise-induced damage (van Putten et al, 2012) and a minimum of 30% of normal dystrophin levels needs to be present uniformly in all myofibers to prevent muscular dystrophy in humans (Neri et al, 2007). Therefore any potential treatment would need to be administered systemically.…”
Section: Introductionmentioning
confidence: 99%